Initial Results of a Safety and Feasibility Study of Auditory Brainstem Implantation in Congenitally Deaf Children. Issue 2 (February 2017) - Wilkinson, Eric P.; Eisenberg, Laurie S.; Krieger, Mark D.; Schwartz, Marc S.; Winter, Margaret; Glater, Jamie L.; Martinez, Amy S.; Fisher, Laurel M.; Shannon, Robert V.
Abstract : Objective: To determine the safety and feasibility of the auditory brainstem implant (ABI) in congenitally deaf children with cochlear aplasia and/or cochlear nerve deficiency. Study Design: Phase I feasibility clinical trial of surgery in 10 children, ages 2 to 5 years, over a 3-year period. Setting: Tertiary children's hospital and university-based pediatric speech/language/hearing center. Intervention(s): ABI implantation and postsurgical programming. Main Outcome Measure(s): The primary outcome measure is the number and type of adverse events during ABI surgery and postsurgical follow-up, including behavioral mapping of the device. The secondary outcome measure is access to and early integration of sound. Results: To date, nine children are enrolled. Five children have successfully undergone ABI surgery and postoperative behavioral programming. Three children were screen failures, and one child is currently undergoing candidacy evaluation. Expected adverse events have been documented in three of the five children who received the ABI. One child experienced a cerebral spinal fluid leak, which resolved with lumbar drainage. One child demonstrated vestibular side effects during device programming, which resolved by deactivating one electrode. One child experienced postoperative vomiting resulting in an abdominal radiograph. Four children have completed their 1-year follow-up and have speech detection thresholds of 30 to 35 dB HL. Scores on the IT-MAIS/MAIS range from 8 to 31 (out of a total of 40), and the children are demonstrating some ability to discriminate between closed-sets words that differ by number of syllables (pattern perception). Conclusion: ABI surgery and device activation seem to be safe and feasible in this preliminary cohort. Abstract : Supplemental Digital Content is available in the text